Interneuron control of hippocampal oscillations - Allen, Kevin; Monyer, Hannah (Current opinion in neurobiology, 2015)
GABAergic interneurons in the hippocampus coordinate neuronal activity that gives rise to network oscillations. In this article we present advances in our understanding of how different classes of hippocampal interneurons contribute to distinct hippocampal network oscillations. We focus on two main experimental approaches that were recently applied in awake animals. Firstly, we review experiments in which selective activation or inhibition of subgroups of GABAergic interneurons was used to asses their contribution to network oscillations. Secondly, we present work that provides a first characterization of the firing activity of anatomically identified interneurons in the hippocampus of behaving animals.
Online 18 September 2014
Gesehen am 22.07.2020